“Strategi Pembelajaran Adaptif bagi Anak Berkebutuhan Khusus di Sekolah Dasar: Systematic Literature Review 2020-2025” - Mukti Hariyadi; Liftiah Liftiah; Ali Formen (Jurnal Prasasti Ilmu, 2026)
This study aims to synthesize research on adaptive learning strategies for children with special needs in elementary schools. Using a Systematic Literature Review guided by PRISMA, this study analyzed 32 articles published between 2020 and 2025 from Google Scholar, Scopus, SpringerLink, ScienceDirect, DOAJ, and SINTA. The data were analyzed through thematic synthesis. The findings show that the most common strategies include differentiated instruction, adaptive curriculum, game-based learning, and adaptive learning technologies. These strategies support learning outcomes, motivation, participation, social skills, and self-regulation. Implementation depends on teacher competence, school support, technological readiness, curriculum flexibility, and student characteristics. This review contributes to inclusive education by mapping current research trends and identifying practical factors that influence adaptive learning implementation in elementary schools.